Hypostatic ulcers in 47,XXY Klinefelter's syndrome - Verp, Marion S (1983)
Hypostatic leg ulcers, probably secondary to vascular insufficiency, were observed in two adult men with 47,XXY Klinefelter's syndrome. The association between leg ulcers and 47,XXY Klinefelter's syndrome deserves increased attention because knowledge of the association may alert clinicians to an otherwise unsuspected chromosome abnormality.